Study on the FAME oxidation and thermal stability of biodiesel / Navin Ramasamy - Navin, Ramasamy (2012)
Fatty acids methyl esters (FAME) have a major effect in displacing Diesel fuel of crude oil origin and also to minimize the emission of gases which contribute to the global warming phenomenon. Furthermore, FAME easily biodegrades as compared to the fossil fuel. In order to investigate the oxidation of stability of FAME, there are various methods which can be employed, namely FAME in relation to European standard PN EN 14214. This research project produces a critical result of determination of FAME oxidation stability with different type of biodiesel sample. From this research report, the most suitable biodiesel that can be used for consideration for alternative renewable energy would be jatropha biodiesel. Jatropha biodiesel good in thermal stability, can maintain fuel properties in higher temperature, low acid value, low density, has a higher total base number, low viscosity which indicates that jatropha biodiesel is thermally stable and has a longer period of oxidation rate.This research is very important for further biodiesel development in our country to develop in future pure biodiesel fuel or partially biodiesel fuel mix with crude oil.